Epigallocatechin-gallate loaded BSA nanoparticles as innovative anti-inflammatory agents in immature macrophages - Martano, Simona; Cascione, Mariafrancesca; Giotta, Livia; Rizzello, Loris; Di Corato, Riccardo; Leporatti, Stefano; Rinaldi, Rosaria; De Matteis, Valeria (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe development of innovative anti-inflammatory therapies is critical for addressing chronic inflammatory diseases and cancer. Epigallocatechin gallate (EGCG), a polyphenolic compound with strong antioxidant and anti-inflammatory properties, suffers from limited stability and bioavailability. Bovine Serum Albumin Nanoparticles (BSA-NPs), due to their biodegradability, non-toxicity, and high binding capacity, represent a powerful delivery system for bioactive compounds.MethodsEGCG-loaded BSA nanoparticles (EGCG@BSA-NPs) were synthesized via the desolvation method. The nanoparticles were characterized by Transmission Electron Microscopy (TEM), Dynamic Light Scattering (DLS), ζ-potential analysis, Fourier-transform infrared spectroscopy (FTIR), and UV-Vis spectroscopy. Encapsulation efficiency and antioxidant capacity were assessed by Trolox equivalent antioxidant capacity (TEAC) assays. The anti-inflammatory potential was evaluated in immature macrophages (THP-1 cells) by assessing NF-κB nuclear translocation and the stimulation of proinflammatory cytokines IL-8 and TNF-α.ResultsMorphological and physicochemical analyses confirmed the successful formation of spherical EGCG@BSA-NPs with improved size uniformity and controlled surface charge. Antioxidant assays demonstrated enhanced radical scavenging activity compared with unloaded BSA-NPs and free EGCG. Cellular studies showed that EGCG@BSA-NPs reduced NF-κB nuclear translocation and decreased IL-8/TNF-α secretion, highlighting their anti-inflammatory efficacy.DiscussionThese findings suggest that EGCG@BSA-NPs are an effective nanoplatform for the controlled delivery of polyphenolic compounds. By improving stability and enhancing bioactivity, they hold significant promise in modulating macrophage function and reducing inflammation, thereby supporting their potential use in chronic inflammatory disease and cancer therapy.